The Role of Financial Technology (FinTech) in Enhancing MSMEs’ Access to Finance: A Study from the Perspective of Financial Management - Safitri, Maria; Muharam, Harjum; Pangestuti, Irene Rini Demi (Jurnal Ilmiah Global Education, 2025)
The expansion of financial technology (FinTech) has changed the way that MSMEs, and the potential entrepreneurs behind them, can access capital, especially in emerging markets, where traditional financial services availability is constrained. Notwithstanding the growing accessibility of digital financial services, a large number of MSMEs still struggle to engage with these technologies; their barriers including low levels of financial literacy, poor digital preparation, and internal decision-making obstacles. This study tries to explore the effects of FinTech adoption on MSMEs access to finance, with focus on the mediating effect of financial literacy and the moderating role of financial behavior and trust. A quantitative causal-explanatory research design was employed using primary data that were gathered using structured questionnaires from Indonesian MSME owners transacting in FinTech platforms. The relationships between the main constructs were investigated through Structural Equation Modeling (SEM). The findings indicate that financial literacy and internal financial management fully mediate the effect of FinTech on financing outcomes, and digital trust and risk perception moderate the relationship. The results provided are consistent with the utilization of the COR Theory in understanding digital financial behavior among MSMEs reiterating that technology itself is not enough if cognitive and behavioral resources are not enabled. This study provides practical implications for policymakers and FinTech developers who seek to shape inclusive financial systems and also demonstrates the need to incorporate financial education in digital innovations' strategy to build greater economic resiliency of MSMEs